2013
DOI: 10.1107/s1600536813001499
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of trilithium divanadium(III) tris(orthophosphate), Li3V2(PO4)3, based on single-crystal X-ray data

Abstract: The structure of Li3V2(PO4)3 has been reinvestigated from single-crystal X-ray data. Although the results of the previous studies (all based on powder diffraction data) are comparable with our redetermination, all atoms were refined with anisotropic displacement parameters in the current study, and the resulting bond lengths are more accurate than those determined from powder diffraction data. The title compound adopts the Li3Fe2(PO4)3 structure type. The structure is composed of VO6 octa­hedra and PO4 tetra­h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…It has been reported that the positions of Li + ions in Li 3 V 2 (PO 4 ) 3 can vary depending on the synthetic conditions while those of the V, P, and O atoms comprising the rigid framework remain intact (Yang et al, 2010). The positions of the Li1, Li3, and Li4 sites in this work are very close to those of the ordered Li sites found in Li 3 V 2 (PO 4 ) 3 (Kee & Yun, 2013).…”
Section: S1 Commentsupporting
confidence: 75%
See 2 more Smart Citations
“…It has been reported that the positions of Li + ions in Li 3 V 2 (PO 4 ) 3 can vary depending on the synthetic conditions while those of the V, P, and O atoms comprising the rigid framework remain intact (Yang et al, 2010). The positions of the Li1, Li3, and Li4 sites in this work are very close to those of the ordered Li sites found in Li 3 V 2 (PO 4 ) 3 (Kee & Yun, 2013).…”
Section: S1 Commentsupporting
confidence: 75%
“…The anionic framework of Li 3 Cr 2 (PO 4 ) 3 is the same as that of the previously reported monoclinic Li 3 V 2 (PO 4 ) 3 structure (Kee & Yun, 2013). The general structural features of this phase have been discussed previously (Patoux et al, 2003;Fu et al, 2010).…”
Section: S1 Commentsupporting
confidence: 68%
See 1 more Smart Citation
“…The lattice parameters of the as-prepared C-LVP (a ¼ 8.6080(2) A; b ¼ 8.5939(2) A; c ¼ 14.7263(4) A; b ¼ 125.180(1) ) are much closer to that reported for LVP. 26 The atomic parameters are listed in Table S2 in the ESI. † Isostructural to the monoclinic structure of Li 3 Fe 2 (PO 4 ) 3 (P2 1 /c space group), LVP entails VO 6 octahedrons and PO 4 tetrahedrons, which share their apical O atoms to form a 3D framework.…”
mentioning
confidence: 99%
“…The positions of the Li + ions in the empty channels (voids) vary depending on the synthetic conditions. 26 The as-prepared C-LVP composite electrodes were electrochemically delithiated using both two-electrode Li cells and three-electrode Mg cells. The electrochemical measurements were performed at 55 C, in order to fully delithiate the three Li + from LVP.…”
mentioning
confidence: 99%